1996
DOI: 10.1007/bf00187924
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of sympathetic axons and their structural relationship with vascular smooth muscle

Abstract: This review focuses on the more recent findings of the structure of sympathetic postganglionic axons and the association of their varicose terminals with vascular smooth muscle. These studies have investigated the innervation of a wide range of vessels from different regions of the vasculature in the rat, guinea pig and rabbit and have predominantly used serial sections and computerised three-dimensional reconstructions of entire varicosities. They have shown, contrary to previous studies conducted in the 1960… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
53
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 112 publications
(162 reference statements)
3
53
1
2
Order By: Relevance
“…Fluorescence histochemical estimations of varicosity numbers were also at variance with ultrastructural data, which showed that varicosity numbers were not significantly different between the 2 ages. However as suggested by Luff (1991Luff ( , 1996, the clustering of varicosities observed in the present study may lead to an underestimate of varicosities at the light microscope level. Thus, caution should be taken when using fluorescence histochemistry as the primary method of assessing nerve fibre and varicosity density (van Orden et al 1966 ;Bevan et al 1980 ;Burnstock & Griffith, 1983 ;Luff, 1991 ;Dodge et al 1994).…”
Section: contrasting
confidence: 43%
See 4 more Smart Citations
“…Fluorescence histochemical estimations of varicosity numbers were also at variance with ultrastructural data, which showed that varicosity numbers were not significantly different between the 2 ages. However as suggested by Luff (1991Luff ( , 1996, the clustering of varicosities observed in the present study may lead to an underestimate of varicosities at the light microscope level. Thus, caution should be taken when using fluorescence histochemistry as the primary method of assessing nerve fibre and varicosity density (van Orden et al 1966 ;Bevan et al 1980 ;Burnstock & Griffith, 1983 ;Luff, 1991 ;Dodge et al 1994).…”
Section: contrasting
confidence: 43%
“…Like the reconstructed varicosities from arterioles of 21 d animals, the size and shape of the varicosities varied considerably, as did the size and shape of the VSM contact areas. While VSM cell contact areas were similar in size at 14 and 21 d, they were significantly smaller than those in other blood vessels (Luff, 1996 : 0.58p0.06 µm#, n l 49, from 4 different beds), although they were similar to those observed between varicosities and dilator myoepithelial cells (Hill et al 1993). The average volume of irideal varicosities from 14 d animals was 70 % that of 21 d arterioles, but this was not significant.…”
Section: mentioning
confidence: 64%
See 3 more Smart Citations